Impact of bioethanol impurities on steam reforming for hydrogen production: A review. (17th April 2020) - Sanchez, Nestor; Ruiz, Ruth; Hacker, Viktor; Cobo, Martha
Abstract: Hydrogen fuel cells (H2 –FCs) are promising devices for pollution-free and efficient power production. Renewable H2 from biomass is often produced through catalytic ethanol steam reforming (ESR), which requires a steam/ethanol molar ratio of at least three. The bioethanol obtained by biomass fermentation contains large amounts of water and can be directly subjected to ESR without complex purification steps. However, a wide spectrum of impurities is present in such bioethanol samples, thus complicating the ESR process. Acetic acid, fusel alcohols, ethyl acetate, and sulfur components have been reported as important bioethanol impurities, and also as the main precursors of carbon deposits on the ESR catalyst. On the other hand, amines, methanol, and aldehydes, which are minor bioethanol impurities, have been reported to enhance the H2 production. This review seeks to define alternatives to reduce the above negative impurities and increase the positive ones during biomass pretreatment and fermentation. Additionally, ESR catalysts are reviewed to identify the features that make them more resistant to deactivation. The combination of strategies to control the impurities during biomass pretreatment, fermentation, purification and the development of highly resistant catalysts may allow processes to produce H2 from biomass with a low carbon footprint, rendering H2 –FCs an environmentally friendly technology for power production. Highlights: The major bioethanol impurities are fusel alcohols, acetic acid, and ethyl acetate. These impurities reduce the H2 yield of ESR via carbon deposit formation. Bimetallic catalysts on supports with high OSC inhibit the carbon deposit formation. Minor impurities such as aldehydes and amines enhance the H2 yield during ESR. Metabolic engineering may reduce harmful impurities while increasing harmless ones.